Pharmacognostical, phytochemical and pharmacological aspects of Quisqualis indica: An update - Mayank Kulshreshtha; Karuna Shanker Shukla; Garima Awasthi Tiwari; Manjul Pratap Singh; Anita Singh (Wolters Kluwer Medknow Publications, 2018)
Nature is a big and important source of lots of things, in which plants are the living gifts of nature. Plants play an important role in various fields, but the role of these plants as herbal medicines is a big achievement. Drugs are obtained from plants have very low side effects and very popular in worldwide. Here, this review represents the pharmacology, pharmacognosy, and various molecular aspects of Quisqualis indica which may be helpful in near future based on available published data. This review opens the various doors or acts as a backbone for various researches in near future.